Sistem Patrilineal Pada Hukum Waris Adat Masyarakat Batak (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
Indonesia characterized by its diverse society encompassing various ethnicities, cultures, races, religions, and regional customs, exhibits a distinctive uniqueness. The country features three primary kinship systems patrilineal, matrilineal, and parental or bilateral. These kinship systems significantly impact the lives of indigenous peoples, particularly in the Batak community, which follows the patrilineal system, especially in matters of inheritance. This study aims to analyze the correlation between the patrilineal system and Batak customary law regarding inheritance, as well as explore methods for resolving disputes arising during the inheritance division process according to Batak customary law. The research adopts a normative approach, utilizing a literature study as the method of data collection. The findings indicate a connection between the patrilineal system and inheritance practices within Batak customary law. Moreover, the study highlights two approaches for settling disputes related to Batak customary inheritance non-litigation and litigation.